2021
DOI: 10.1038/s41598-021-88600-1
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic nitrate in groundwater and its health risks in the view of background concentration in a semi arid area of Rajasthan, India

Abstract: An increased nitrate (NO3−) concentration in groundwater has been a rising issue on a global scale in recent years. Different consumption mechanisms clearly illustrate the adverse effects on human health. The goal of this present study is to assess the natural and anthropogenic NO3− concentrations in groundwater in a semi arid area of Rajasthan and its related risks to human health in the different groups of ages such as children, males, and females. We have found that most of the samples (n = 90) were influen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(34 citation statements)
references
References 64 publications
2
31
0
1
Order By: Relevance
“…Statistical analysis revealed that there was a minor significant relationship between groundwater NO 3 − content and Cl − ions in rural groundwater samples (p < 0.001 and r = 0.169), while it was not significant in urban samples (p = 0.848). Previous observations reported positive correlations between nitrate and chloride in rural groundwater (Iwar et al, 2021;Rahman et al, 2021;Yu et al, 2020). They reported that chemical fertilizers or the pollution of feces and livestock waste may elevate the concentration of chlorine ions in groundwater.…”
Section: Nitrate Concentration In Groundwatermentioning
confidence: 96%
See 2 more Smart Citations
“…Statistical analysis revealed that there was a minor significant relationship between groundwater NO 3 − content and Cl − ions in rural groundwater samples (p < 0.001 and r = 0.169), while it was not significant in urban samples (p = 0.848). Previous observations reported positive correlations between nitrate and chloride in rural groundwater (Iwar et al, 2021;Rahman et al, 2021;Yu et al, 2020). They reported that chemical fertilizers or the pollution of feces and livestock waste may elevate the concentration of chlorine ions in groundwater.…”
Section: Nitrate Concentration In Groundwatermentioning
confidence: 96%
“…According to previous studies, the two main routes of nitrate exposure are drinking water and dermal exposure via bathing or swimming in nitrate-contaminated water (Yang et al, 2012). Given that we did not have information about swimming and bathing in the study area, and previous studies such as the study by Yu et al (2020) and Rahman et al (2021) showed that the risk of exposure to this route was very low, in the present study, only the risk assessment of drinking water contaminated with different amounts of nitrate has been investigated. Calculations for non-carcinogenic health risks associated with the consumption of groundwater containing nitrate by the residents were made based on the standard assumptions used in US-EPA risk analysis.…”
Section: Exposure and Health Risk Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Nitrogen, one of the most frequent contaminants in freshwaters, is estimated to have a natural occurrence as nitrate (up to 10 mg/L), but values above this threshold reflect anthropogenic pollution [79][80][81][82]. The natural background of nitrate represents only a relative measure due to the interactions between the rock matrix and water, dissolutions, interactions between different water bodies, chemical and biological processes, retention time, and precipitation [82].…”
Section: Nutrients and The Anthropogenic Impact On The Freshwater Sou...mentioning
confidence: 99%
“…Rahman et al (2021) summarized that the results may be good if the CBE is < ± 5%, and up to ± 10% is acceptable for groundwater. CBEs of most water samples were < ± 5%, although only one sample of N11 showed an acceptable CBE level of + 5.8%.…”
mentioning
confidence: 99%